A Systematic Review of Diagnostic Methods for Pelvic Venous Insufficiency - Dobrzańska, Justyna; Smykiewicz, Karolina; Dziedzic, Mariola; Partyka, Alicja; Chmielowiec, Zuzanna; Wierzejska, Natalia; Fugas, Agnieszka; Michalczewska, Aneta; Nowak, Agnieszka; Pach, Magdalena (Quality in Sport, 2024)
Pelvic venous insufficiency (PVI) is a recognized contributor to chronic pelvic pain (CPP). Diagnosing PVI can be challenging due to its often subtle and non-specific presentation. While both men and women can be affected, PVI is more prevalent in women, potentially due to hormonal fluctuations and the physiological effects of pregnancy. Transabdominal ultrasound (US) remains the first-line non-invasive imaging modality for PVI evaluation. However, magnetic resonance imaging (MRI) and magnetic resonance venography (MRV) play an increasingly important role in confirming the diagnosis, particularly in select patient populations where US findings are inconclusive. This article will delve into the various diagnostic techniques employed for PVI, analyzing their efficacy and limitations to guide optimal diagnostic approach.